Altered cerebrocerebellar functional connectivity in patients with obstructive sleep apnea and its association with cognitive function. Issue 1 (25th August 2021) - Park, Hea Ree; Cha, Jungho; Joo, Eun Yeon; Kim, Hosung
Abstract: Study Objectives: Previous functional MRI studies have reported altered brain networks in patients with obstructive sleep apnea (OSA). However, the extent and pattern of abnormal connectivity were inconsistent across studies, and cerebrocerebellar connections have been rarely assessed. We investigated functional network changes in cerebral and cerebellar cortices of OSA patients. Methods: Resting-state functional MRI, polysomnography, and neuropsychological (NP) test data were acquired from 74 OSA patients (age: 45.8 ± 10.7 years) and 33 healthy subjects (39.6 ± 9.3 years). Connectivity matrices were extracted by computing correlation coefficients from various regions of interest, and Fisher r -to- z transformations. In the functional connections that showed significant group differences, linear regression was conducted to examine the association between connectivity and clinical characteristics. Results: Patients with OSA showed reduced functional connectivity (FC) in cerebrocerebellar connections linking different functional networks, and greater FC in cortical between-network connections in prefrontal regions involving the default mode network (DMN) and the control network. For OSA group, we found no correlation between FC and sleep parameters including lowest SaO2 and arousal index in the connections where significant associations were observed in healthy subjects. FC changes in DMN areas were related to reduced verbal fluency in OSA. Lower local efficiency and lower clustering coefficient of the salience network in the left cerebellum were also observed in OSA. Conclusions: OSA affects mainly the cerebrocerebellar pathway. The disruption of function in these connections are related to sleep fragmentation and hypoxia during sleep. These abnormal network functions, especially DMN, are suggested to participate in cognitive decline of OSA.